NAT yield in blood donors: An observational study - Ankit Sharma; Sunita Bundas; Rashmi Parashar (Journal of Family Medicine and Primary Care)
Introduction: Individual donation nucleic acid testing (ID-NAT) is considered as highly sensitive technology for viral transfusion-transmissible infections (TTIs) in blood donors. The present study was aimed to analyze the results of ID-NAT with special reference to different types of donors, their age, gender, blood group ranges in a tertiary care center in north India. Methodology: The present study was done from 24th June 2019 to 31st December 2021 in Blood Center, Department of Immunohematology and Blood Transfusion, SMS Hospital, Jaipur. A total of 18313 apparently healthy adult donors were included in present study. Result: In 2019 Combined NAT yield was 1 in 754, in 2020 it was 1 in 2368 and in 2021 it was 1 in 741. With Total NAT yield was 1 in 1017 (0.09 %) over a period of study. NAT yield in HBV is 1 in 1077, in HCV 1 in 18313 and no NAT Yield in HIV. Conclusion: NAT testing for hepatitis B provides additional safety because ELISA does not pick up occult hepatitis. The non-seroconverting or delayed seroconverting disease is missed by ELISA alone and can be picked up by NAT.